Boron Nitride Nanotube Addition Enhances the Crystallinity and Cytocompatibility of PVDF-TrFE - Poudel, Anup; Fernandez, Marc A.; Tofail, Syed A. M.; Biggs, Manus J. P. (Frontiers in Chemistry, 2019)
Analysis of the cellular response to piezoelectric materials has been driven by the discovery that many tissue components exhibit piezoelectric behavior ex vivo. In particular, polyvinylidene fluoride and the trifluoroethylene co-polymer (PVDF-TrFE) have been identified as promising piezo and ferroelectric materials with applications in energy harvesting and biosensor devices. Critically, the modulation of the structural and crystalline properties of PVDF-TrFE through annealing processes and the addition of particulate or fibrous fillers has been shown to modulate significantly the materials electromechanical properties. In this study, a PVDF-TrFE/boron-nitride nanotube composite was evaluated by modulated differential scanning calorimetry to assess the effects of boron nitride nanotube addition and thermal annealing on the composite structure and crystal behavior. An increased beta crystal formation [f(β) = 0.71] was observed following PVDF-TrFE annealing at the first crystallization temperature of 120°C. In addition, the inclusion of boron nitride nanotubes significantly increased the crystal formation behavior [f(β) = 0.76] and the mechanical properties of the material. Finally, it was observed that BNNT incorporation enhance the adherence and proliferation of human tenocyte cells in vitro.